Položaj priseljenskih jezikov v Sloveniji - Medvešek, Mojca (Jezik in slovstvo, 2012)
The article deals with the status and use of the languages of immigrants and their descendants in Slovenia. It focuses on five areas: education, culture, religion, the media and the labour market. In addition to the legal and formal framework defining the status of immigrant languages and the opportunities for their development in the areas referred to, empirical data is presented on the actual use of immigrant languages and the perception, on the part of immigrants as well as their offspring, of the use and status of their mother tongues in Slovenia. Despite the state's efforts to promote multilingualism, and its commitment to implementing the language rights of individuals and minority groups in Slovenia, the authors come to the conclusion that, in practice, Slovene society often fails to recognise the wider significance and value of immigrant languages.
Keywords: sociolinguistics; sociolingvistika; jezikovna politika; Slovenia; Slovenija; priseljenci; slovenščina kot drugi/tuji jezik; jeziki priseljencev; materinščina; first language; izobraževanje; education; culture; kultura